2020
DOI: 10.1177/0891988720944237
|View full text |Cite
|
Sign up to set email alerts
|

AD-Related CSF Biomarkers Across Distinct Levels of Cognitive Impairment: Correlations With Global Cognitive State

Abstract: Aim: Associations between cerebrospinal fluid (CSF) biomarkers of Alzheimer’s disease (AD) with the severity of cognitive impairment are unclear. We examined the correlations between CSF biomarkers and cognitive performance in the AD continuum. Methods: We studied 143 elderly patients: cognitively unimpaired (n = 51), mild cognitive impairment (MCI) amnestic (n = 55) and nonamnestic (n = 20), and mild AD (n = 17) assessed with the Cambridge Cognitive Test (CAMCOG). We correlated total CAMCOG and its subdomains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Another explanation is that an NABD accompanied by substantial axonal neurodegeneration and known to reveal long-term cognitive decline resembling that observed in AD patients should be distinguished from an autoimmune encephalopathy entity. CSF tau protein is known to be interrelated with cognitive functions in AD and other cognitive impairment phases ( 23 ), but so far, no study has investigated its correlation in NABD. As tau protein is elevated when axonal neurodegeneration occurs, it is not surprising that both the long-term and yearly decline of cognitive dysfunction is related to total tau protein.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that an NABD accompanied by substantial axonal neurodegeneration and known to reveal long-term cognitive decline resembling that observed in AD patients should be distinguished from an autoimmune encephalopathy entity. CSF tau protein is known to be interrelated with cognitive functions in AD and other cognitive impairment phases ( 23 ), but so far, no study has investigated its correlation in NABD. As tau protein is elevated when axonal neurodegeneration occurs, it is not surprising that both the long-term and yearly decline of cognitive dysfunction is related to total tau protein.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in demographic and clinical information were found across the two groups. The AD population was older than the lvPPA population and the two groups comprised more women than men, corresponding to the pathologies’ demography described in the literature [ 50 ]. They had an equivalent cognitive level as shown by the MMSE score ( p = 0.709).…”
Section: Resultsmentioning
confidence: 99%
“…Lumbar punctures allowed the extraction of CSF and measurement of AD relative biomarkers. Measures of β 42-Amyloïd peptide, total tau and phospho-tau protein concentrations were collected [ 49 , 50 ]. The standard for each protein corresponds to 700–1800 pg/mL, 130–6001 pg/mL and 20–60 ng/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy could be due to different sensitivity in the assays used in the two studies (a fully automated Lumipulse assay (Fujirebio, Inc.) in the present study and an enzyme-linked immunosorbent assay (ELISA) assay (ADx; Sutphen et al, 2015) in the previous study), or differences in study participants. Correlations between behavioral measures and either CSF Aβ42 or CSF Tau are common in the literature (Ibarra et al, 2021; Milà-Alomà et al, 2020). Finally, Gollan and colleagues reported that the oldest-old participants with the most AD-like biomarkers produced the most autocorrect errors (Gollan, Smirnov, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%